Neuroimmunological effects of omega-3 fatty acids on migraine: a review - Chen, Ting-Bin; Yang, Cheng-Chia; Tsai, I-Ju; Yang, Hao-Wen; Hsu, Yung-Chu; Chang, Ching-Mao; Yang, Chun-Pai (Frontiers in Neurology, 2024)
Migraine is a highly prevalent disease worldwide, imposing enormous clinical and economic burdens on individuals and societies. Current treatments exhibit limited efficacy and acceptability, highlighting the need for more effective and safety prophylactic approaches, including the use of nutraceuticals for migraine treatment. Migraine involves interactions within the central and peripheral nervous systems, with significant activation and sensitization of the trigeminovascular system (TVS) in pain generation and transmission. The condition is influenced by genetic predispositions and environmental factors, leading to altered sensory processing. The neuroinflammatory response is increasingly recognized as a key event underpinning the pathophysiology of migraine, involving a complex neuro-glio-vascular interplay. This interplay is partially mediated by neuropeptides such as calcitonin gene receptor peptide (CGRP), pituitary adenylate cyclase activating polypeptide (PACAP) and/or cortical spreading depression (CSD) and involves oxidative stress, mitochondrial dysfunction, nucleotide-binding domain-like receptor family pyrin domain containing-3 (NLRP3) inflammasome formation, activated microglia, and reactive astrocytes. Omega-3 polyunsaturated fatty acids (PUFAs), particularly eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), crucial for the nervous system, mediate various physiological functions. Omega-3 PUFAs offer cardiovascular, neurological, and psychiatric benefits due to their potent anti-inflammatory, anti-nociceptive, antioxidant, and neuromodulatory properties, which modulate neuroinflammation, neurogenic inflammation, pain transmission, enhance mitochondrial stability, and mood regulation. Moreover, specialized pro-resolving mediators (SPMs), a class of PUFA-derived lipid mediators, regulate pro-inflammatory and resolution pathways, playing significant anti-inflammatory and neurological roles, which in turn may be beneficial in alleviating the symptomatology of migraine. Omega-3 PUFAs impact various neurobiological pathways and have demonstrated a lack of major adverse events, underscoring their multifaceted approach and safety in migraine management. Although not all omega-3 PUFAs trials have shown beneficial in reducing the symptomatology of migraine, further research is needed to fully establish their clinical efficacy and understand the precise molecular mechanisms underlying the effects of omega-3 PUFAs and PUFA-derived lipid mediators, SPMs on migraine pathophysiology and progression. This review highlights their potential in modulating brain functions, such as neuroimmunological effects, and suggests their promise as candidates for effective migraine prophylaxis.